Assessment of patient's satisfaction with pharmaceutical care services in community pharmacies in the United Arab Emirates - Suleiman Ibrahim El-Sharif; Nora Abd Alrahman; Nouray Khaled; Noor Sayah; Esraa Gamal; Azza Mohamed (Archives of Global Professionals, 2017)
Objective: To determine some aspects of patient's satisfaction of pharmaceutical services provided by the community pharmacist. To assess consumer's attitude towards the services provided in the community pharmacy. Methods: An anonymous pre-piloted questionnaire-based study was conducted in the various Emirates of the United Arab Emirates. Data were analyzed using SPSS and results were expressed as frequency and percentage of respondents. Results: The response rate was 93.8% with more female than male respondents. The majority of participants were Arabs (80.5%) of young age and with no medical background. Slightly more than half of the respondents (198, 52.8%) visited the pharmacy to collect prescriptions, and 50.5% of them were able to collect the prescriptions straight away. Only 31.7% of respondents visited the pharmacy to purchase items and of these group 289 (77.1%) were satisfied with the pharmacist's help. When asked to describe their usual pharmacist, "experienced," "trustworthy," and "confident" were the descriptions given by 27.7%, 22.9%, and 67.9% respondents, respectively. The majority (74.1%) of respondents agreed that the pharmacist delivers their medicines in a polite way, and 43.7% agreed that the instructions were clearly labeled by the pharmacist on each medication and 24.5% agreed that the pharmacists provided them with information on drug storage. About 38.4% agreed that the place of pharmaceutical counseling respects their privacy. Conclusion: Results of the present study showed a general patient's satisfaction of the help provided by the community pharmacist. However, the pharmacist needs to fully practice his/her role to the advantage of the patients and the latter needs to be aware of what to expect and demand from the community pharmacist.